Critical Theories of Globalization - el-Ojeili, C. author. aut Link
VIII, 241 p.
Keywords: This accessible text provides a comprehensive overview of globalization and its consequences from the perspective of social and political critical theory. Thematic chapters provoke student inquiry and the book shows how the views of critical theorists are crucial to understanding the global processes shaping the world today.